Segregation Analysis of SSR, SNP, and AFLP Markers in F2 Population of Solanum lycopersicum × S. arcanum (Analisis Segregasi Marka SSR, SNP, dan AFLP pada Populasi F2 Persilangan Solanum lycopersicum × S. arcanum) - Chaerani Chaerani; R. E. Voorrips (Jurnal AgroBiogen, 2015)
Distorted marker segregation is a common phenomenon in interspecific cross of various crops. Previous mapping study of earlyblight fungus (Alternaria solani) resistance loci showed 52% marker distortion in the genetic linkage map of 176 F2 progeniesderived from Solanum lycopersicum cv. Solentos × S. arcanum LA2157. The objectives of this study were to analyze in detail themarker segregation in the map and to determine the cause of segregation distortion by calculating the allele and genotypefrequencies of each marker. Out of 371 mapped markers, 192 markers deviated from the expected Mendelian ratio of 1 : 2 : 1.Distorted markers occurred in all chromosomes, ranging from 1% to 92%. Surplus of S. arcanum homozygotes contributed mostto the skewness (40%), followed by heterozygotes (18%), and S. lycopersicum homozygotes (5%). The allele frequencies of 152markers deviated from the expected allele homogeneity frequency, indicating that their segregation might be affected bygamethophytic selection. Sixty-one markers deviated from the expected F2 genotype frequency distribution, indicating that theirsegregation might be influenced by zygotic selection. Thirty-seven of the distorted markers showed deviation from expectedfrequencies of allele homogeneity and F2 genotype frequency distribution. Distorted markers can be retained in linkage analysissince chromosomal regions containing distorted markers showed linkage with early blight fungus resistance loci. Furtheridentification of the mechanism contributing segregation distortion requires detailed and extensive mapping studies.